Latent Nucleophiles in Lewis Base Catalyzed Enantioselective N‐Allylations of N‐Heterocycles. Issue 31 (1st July 2019) - Zi, You; Lange, Markus; Schultz, Constanze; Vilotijevic, Ivan
Abstract: Latent nucleophiles are compounds that are themselves not nucleophilic but can produce a strong nucleophile when activated. Such nucleophiles can expand the scope of Lewis base catalyzed reactions. As a proof of concept, we report that N ‐silyl pyrroles, indoles, and carbazoles serve as latent N‐centered nucleophiles in substitution reactions of allylic fluorides catalyzed by Lewis bases. The reactions feature broad scopes for both reaction partners, excellent regioselectivities, and produce enantioenriched N ‐allyl pyrroles, indoles, and carbazoles when chiral cinchona alkaloid catalysts are used. Abstract : Double activation required : Latent nucleophiles enlarge substrate scopes and improve selectivities in Lewis base catalysis. N ‐Silyl pyrroles, indoles, and carbazoles serve as latent N‐centered nucleophiles in highly selective enantioselective Lewis base catalyzed substitutions of allylic fluorides.